Penerapan Media Komik Religi Untuk Meningkatkan Kemampuan Membaca Siswa Mata Pelajaran Bahasa Indonesia Kelas II SDN 111 Pekanbaru - Junindra Darisky Saputra; Sakban Sakban; Wismanto Wismanto (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
Religious comic media is one of the media that uses visual illustrated stories to improve student’s reading skills through characters and with islamic nuances. The problems in this research are (1) what are the application in the religious comic media to improve student’s reading skills (2) what are the application in the religious comic media outcomes for improve student’s reading skills in Bahasa Indonesia lesson (3) what are the constraint for implementing the religious comic media for improve student’s reading skilss in Bahasa Indonesia lesson in class II SDN 111 Pekanbaru? This research includes Classroom Action Research (PTK) which was carried out in two cycle. Each cycle consists of four stages, namely design, implementation, observation, and reflection. The subjects in this research were class II students at SDN 111 Pekanbaru totaling 38 students. Research data was obtained using teacher and student observation sheets and student test results, then this data was analyzed using a precentage formula. The research results obtained are (1) teacher activity incycle1using religious comic media from 62% to 83% in cycle 2, (2) student activity in cycle 1 using the religious comic media 60% to 85% in cycle 2 and (3) student’s reading skills outcomes in Bahasa Indonesia lesson in cycle 1 using the religious comic media 60% to 79% in cycle 2. This shows that the student’s reading skill outcomes for Bahasa Indonesia lesson using the religious comic media show very positive results. Based on the results of this research, it can be concluded that by implementing the religious comic media, student’s reading skilss outcomes and teacher’s abilities can improve more better.